Underpricing of venture-backed and non venture-backed IPOs: Germany's Neuer Markt - Stefanie A. Franzke (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
This paper analyzes a comprehensive data set of 160 non venture-backed, 79 venture-backed and 61 bridge financed companies going public at Germany's Neuer Markt between March 1997 and March 2002. I examine whether these three types of issues differ with regard to issuer characteristics, balance sheet data or offering characteristics. Moreover, this empirical study contributes to the underpricing literature by focusing on the complementary or rather competing role of venture capitalists and underwriters in certifying the quality of a company when going public. Companies backed by a prestigious venture capitalist and/or underwritten by a top bank are expected to show less underpricing at the initial public offering (IPO) due to a reduced ex-ante uncertainty. This analysis provides evidence to the contrary: VC-backed IPOs appear to be more underpriced than non VC-backed IPOs.
urn:nbn:de:hebis:30-9785
Keywords: G24; G32; 330; Venture Capital; Underwriter; Initial Public Offering; Underpricing; Neuer Markt